Suppression of weed and insect populations by living cover crop mulches in organic squash production - Bruce, Dylan; Silva, Erin M.; Dawson, J. C. (Frontiers in Sustainable Food Systems, 2022)
Living mulch systems can provide multiple agronomic and ecosystem benefits, including reducing erosion and decreasing weed and pest pressure. However, inconsistent yields and lack of best practices for weed and pest management have contributed to their lack of adoption by farmers. In 2018 and 2019, living mulch practices for organic zucchini (Cucurbita pepo L.) production were assessed in Wisconsin on certified organic land. Living mulches of Dutch white clover (Trifolium repens), annual ryegrass (Lolium multiflorum), and a mix of Dutch white clover and annual ryegrass were compared with full tillage cultivated ground and straw mulch controls for effect on yield, fruit marketability, weed and pest counts, and weed management time. Mixed species living mulch, cultivated, and straw mulch treatments were consistently higher yielding than clover treatments, while ryegrass had variable results. No differences were observed in the number of squash bug (Anasa tristis) egg clusters per plant across mulch treatments, but clover treatments had fewer adult squash bugs, with ryegrass and mixed species living mulches also trending lower. Lower counts of striped cucumber beetles (Acalymma trivittatum) were also observed in living mulch treatments. Ryegrass and mixed species living mulches were generally more weed suppressive than clover and cultivated aisles, although living mulch treatments generally had more weeds than straw mulched aisles, apart from comparable suppression of grass weeds for ryegrass in 2019. Time required for weed management was greater for the living mulch treatments than straw, while cultivated treatments took longer to manage than all other treatments in 2019 and longer than ryegrass and straw in 2018. Despite higher weed counts in clover than in cultivated aisles in 2019, all living mulches required less time for weed management than cultivation, indicating that managing living mulches with mowing can be more efficient than hand cultivation, even with higher weed counts. Our results support previous evidence that certain living mulch species may reduce pest and weed pressure, but also reinforces that living mulch systems can negatively impact yield depending on species selection and environment.